Mitología andina :formas de entender el mundo y la vida en la sociedad quiteña. - Minda Herrera, Pamela Moncerrath (2016)
Mythology and Andean ancestral issues have gotten blurred due to the current world westernization so that the phenomena described as a folkloric vision of Andean knowledge and practices has had as a result that these elements have been dissociated from their pragmatic meaning. Even if interculturality is present more than ever, many times is just a label with political purposes because, as it will be demonstrated, the Andean world and its appropriation generate great expectation and notice. It is somehow possible to say that interculturality does not stand for a real practice as far as respecting another culture’s elements does not necessarily imply an exchange. This academic article will highlight some failures that appear when topics such as ancestral, mythological, Andean and even intercultural ones are addressed, taking into account basic education in Quito, in reference also to the constitutional and legal system which is nowadays current in the whole Ecuadorian territory.